An Online Observational Study of Patients With Olfactory and Gustory Alterations Secondary to SARS-CoV-2 Infection - Gómez-Iglesias, Patricia; Porta-Etessam, Jesús; Montalvo, Teresa; Valls-Carbó, Adrián; Gajate, Vicente; Matías-Guiu, Jordi A.; Parejo-Carbonell, Beatriz; González-García, Nuria; Ezpeleta, David; Láinez, José Miguel; Matías-Guiu, Jorge (Frontiers in Public Health, 2020)
Introduction. Since the beginning of the COVID-19 epidemic caused by SARS-CoV-2 virus, olfactory alterations have been observed at a greater frequency than in other coronavirus epidemics. While olfactory alterations may be observed in patients with rhinovirus, influenza virus, or parainfluenza virus infection, they are typically explained by nasal obstruction with mucus or direct epithelial damage; in the case of SARS-CoV-2, olfactory alterations may present without nasal congestion with mucus. We performed a study of patients presenting olfactory/gustatory alterations in the context of SARS-CoV-2 infection in order to contribute to the understanding of this phenomenon. Material and methods. We performed a descriptive, cross-sectional, observational study of the clinical characteristics of olfactory/gustatory alterations using a self-administered, anonymous online questionnaire. Results. A total of 909 patients with SARS-CoV-2 infection and olfactory/gustatory alterations responded to the questionnaire in the 4-day data collection period; 90.65% reported simultaneous olfactory and gustatory involvement. Patients’ responses to the questionnaire revealed ageusia (64.1% of respondents), hypogeusia (28.2%), dysgeusia (2.4%), anosmia (82.8%), hyposmia (15.6%), and dysosmia (0.9%). Fifty-four percent did not report concomitant nasal congestion or mucus. Conclusion. Olfactory alterations are frequent in patients with SARS-CoV-2 infection and are associated with nasal congestion in only half of cases.